1991
DOI: 10.1111/j.1476-5381.1991.tb12215.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between lipolysis and cyclic AMP generation mediated by atypical β‐adrenoceptors in rat adipocytes

Abstract: 1 The nature of the fi-adrenoceptor(s) mediating adenylyl cyclase activation in rat adipocyte ghosts by (-)-isoprenaline and the lipolytically selective fi-adrenoceptor agonist, BRL 37344, was investigated by use of the fli-selective antagonist, CGP 20712A. The results were compared with lipolysis in adipocytes.2 While in lipolysis BRL 37344 was a full and 10 times more potent agonist than (-)-isoprenaline, in adenylyl cyclase activation similar pD2 values for both agonists were found. BRL 37344 was only a par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 16 publications
5
19
0
Order By: Relevance
“…However, the Kd values in Table 3 are very similar to those recently reported in 3T3F442A cells by Feve et al [32] who demonstrated, on the basis of both pharmacological and mRNA studies, the large predominance of the newly discovered b3-adrenoceptor subtype [33] in these cells. Our results thus provide further support to recent suggestions that rodent adipocytes possess the b3-adrenoceptor subtype [34,351. However, comparison of the lipolytic potency of the selective f13-adrenergic agonist BRL37344 failed to reveal any significant difference between epididymal and femoral subcutaneous deposits.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, the Kd values in Table 3 are very similar to those recently reported in 3T3F442A cells by Feve et al [32] who demonstrated, on the basis of both pharmacological and mRNA studies, the large predominance of the newly discovered b3-adrenoceptor subtype [33] in these cells. Our results thus provide further support to recent suggestions that rodent adipocytes possess the b3-adrenoceptor subtype [34,351. However, comparison of the lipolytic potency of the selective f13-adrenergic agonist BRL37344 failed to reveal any significant difference between epididymal and femoral subcutaneous deposits.…”
Section: Discussionsupporting
confidence: 81%
“…The half-maximal stimulation (EC,,) for (-)-epinephrine was reached at about 0.2 0.06 pM in the two anatomical sites. The same was true when the ECso values for (-)-isoproterenol and BRL37344, a selective agonist for the fat cell atypical P-adrenoceptor [20], were compared. However, BRL37344 was more potent with epididymal and femoral subcutaneous adipocytes (EC50, 0.49 & 0.17 nM and 0.83 f 0.15 nM, respectively) than (-)-isoproterenol (EC,,, 1.68 f 0.38 nM and 3.11 & 0.64 nM, respectively).…”
Section: Lipolytic Activitymentioning
confidence: 87%
“…The most extensive studies of P3-adrenoceptor-mediated cyclic AMP responses are those which have been conducted on rat adipose tissue (Granneman, 1990;Hollenga et al, 1991a,b). This tissue can be stimulated by BRL 37344 and in the presence of (-)-isoprenaline, gives a bi-phasic response which is resistant to blockade by either CGP 20712A or ICI 118551, yielding pA2 values of 4.53 (Hollenga et al, 1991b) and 5.49 (Hollenga & Zaagsma, 1989) respectively. None of these features were observed in the present study, suggesting that P3-adrenoceptors are not expressed at a functional level in either bovine skeletal muscle or adipose tissue membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Ref. 37), often under conditions where, for example, forskolin-derived cAMP and cAMP derived from hormonal stimulation apparently do not induce the final cellular response with the same potency, i.e. a situation akin to the one described here for brown fat cells.…”
Section: Discussionmentioning
confidence: 99%